Improvement of merchandising assessment of fresh tomatoes and formation of the consumer properties of the products of their processing - Одарченко, Дмитро Миколайович; Сподар, Катерина Вікторівна; Одарченко, Микола Семенович (Technology audit and production reserves, 2015)
The article is devoted to scientific substantiation and improvement merchandising assessment of fresh tomatoes and the formation of consumer properties their products. There were developed and scientifically substantiated methods and parameters of the new method of sample preparation of plant raw materials to the merchandising analysis, the main feature of which is to obtain a liquid phase by separating the shredded pulp into fractions via a cyclic freezing and centrifugation, which is characterized by reversibility of phase with relating to the operations of freezing and thawing. Based on the basic provisions of a scientific hypothesis about the use of the liquid phase for further research, which is the representative and includes qualitative information on the status and properties of all the object of study as a whole, and applying to it the corresponding sensitive methods, we can draw conclusions about supplies feedstock to the tomatoes of open or protected ground and, therefore, their qualitative composition. On the basis of the research it was found that the optical, electrophysical, thermodynamic and cryoscopic methods can determine the conditions of cultivation of tomatoes. So it was determined that the liquid phase from the ground tomatoes have more abrupt change of the current in two times in comparison with the greenhouse. Cryoscopy confirmed that the average molar mass of solute (μ) in the liquid phase of ground tomatoes in 1,6 times higher than the liquid phase of greenhouse tomatoes. The research results of the liquid phase of pepper showed that the average molar mass for soil types is more than the value of this indicator set for the greenhouse in 3,6 times. Research of the optical properties of the liquid phases of vegetables was found that the angle of light scattering in the liquid phase of a fresh greenhouse tomatoes 10...15 % more than the ground. Consumer properties of the obtained vegetable liquid and solid phases were studied, changes in their cold storage were marked. Their functional and technological properties and the ways of further use in the food industry were empirically determined and proposed.